Effects of different spraying periods and concentrations of paclobutrazol on the lodging resistance and yield of high-quality japonica rice - Zhao, Qi; Xiong, Ruoyu; Tang, Jianhao; Yang, Ruifang; Cao, Liming; Bai, Jianjiang (Frontiers in Agronomy, 2025)
IntroductionLodging is a critical limiting factor affecting stable rice production in the lower reaches of the Yangtze River in China.MethodsThis study aims to clarify the optimal spraying period and concentration of paclobutrazol for high-quality japonica rice by examining its effects on the mechanical, morphological, and metabolic characteristics of the stem. A clean water treatment (CK) was established alongside five spraying periods (S1: July 19; S2: July 26; S3: August 2; S4: August 9; S5: August 16) with three spraying concentrations (LP: 100 mg L-1; MP: 200 mg L-1; HP: 300 mg L-1).Results and discussionThe results indicate that the MP treatment during the S4 period resulted in a yield increase of 2.3–11.8% while reducing the lodging index by 15.8-25.5%. In the early stages of spraying (S1, S2 and S3), the lodging resistance of rice was primarily enhanced by reducing plant height, but led to a significant decrease in the spikelets per panicle and grain filling, ultimately resulting in reduced yield. In the later stages of spraying (S4 and S5), lodging resistance was mainly improved by increasing internode diameter and culm wall thickness, which concurrently resulted in a significant increase in the grain filling. Although high concentrations of paclobutrazol in each period can reduce the lodging index, they are not conducive to yield formation. Correlation analysis revealed a significant negative correlation between the lodging index and both the internode diameter and the culm wall thickness. Non-target metabolism indicated that the significant increase in mandelonitrile and sarcosine content within cyanoamino acids metabolism, and glycine, serine, and threonine metabolism during S4, might be the primary metabolic factors promoting the development and thickness of stem walls. Additionally, the increase in pheophytin-a in porphyrin and chlorophyll metabolism, along with leucine in valine, leucine, and isoleucine degradation, may be the key contributors to the enhancement of rice lodging resistance and stable yield when treated with an appropriate concentration of paclobutrazol.